INNOVATIVE TEACHING METHODOLOGIES FOR MODERN ENGLISH EDUCATION IN SECONDARY SCHOOLS - Xaydarova Muattar Iskandarovna (Web of Journals Publishing, 2025)
This research paper explores innovative teaching methodologies that enhance English language education in modern secondary schools. The study discusses the integration of digital learning tools, communicative approaches, task-based learning, and blended learning environments. It highlights how these methods foster creativity, critical thinking, and intercultural communication among students. The findings indicate that adopting modern pedagogical innovations significantly improves students’ motivation and learning outcomes in English education.
Keywords: Innovative teaching; communicative approach; blended learning; digital literacy; English education; task-based learning; secondary school pedagogy.